Concept Building and Basic Statistical Analysis for Inland Fisheries Management" ICAR-CIFRI, Barrackpore, 3 -10 August 2018 - Raman, R. K. (Journal of the Inland Fisheries Society of India, 2019)
Concept Building and Basic Statistical Analysis for InlandFisheries Management" ICAR-CIFRI, Barrackpore, 3 -10August 2018